Faith on the move toward a theology of migration in Asia - Baggio, Fabio; Brazal, Agnes M. (Theology and religious studies series / Agnes M. Brazal, series editor, 2008)
"This is the first work on migration in Asia that deftly blends sociology, anthropology, philosophy, theology, and spirituality to show that migration, now a universal phenomenon, thanks in part to globalization, must be a constant concern of the Church?s mission since it is an expression of the Church?s catholicity and a demand for justice. The essays are uniformly well researched and well written and provide a rich trove of empirical data and theological insights. Faith on the Move is required reading for all Church leaders and those engaged in the ministry with migrants not only in Asia but everywhere."--Prof. Peter C. Phan.